Comparison of nutrient use efficiency, antioxidant assay, and nutritional quality of butter-head lettuce (Lactuca sativa L.) in five cultivation systems - Tunio, Mazhar H.; Gao, Jianmin; Mohamed, Tarek M. K.; Ahmad, Fiaz; Abbas, Irfan; Shaikh, Sher Ali (International Journal of Agricultural and Biological Engineering, 2023)
A greenhouse experiment was conducted to evaluate the comparison of nutrient use efficiency, antioxidant assay, and nutritional quality of butter-head lettuce in five cultivation systems. For this experimental study, a split-boxes experimental arrangement in a completely randomized design (CRD) with three aeroponics systems (high pressure (T1), low pressure (T2), and ultrasonic nozzle (T3)), hydroponic system (T4), and conventional cultivation system (T5) was designed. The analyses of variance (ANOVA) were employed to assess yield, chlorophyll content, relative water content (RWC), nutrient use efficiency (NUE), 2,2-Diphenyl-1-picrylhydrazyl (DDPH), Hydrogen Peroxide (H2O2), Ferric Reducing Antioxidant Power (FRAP), total phenolic (TPC), flavonoid content (TFC) and nutritional quality of butter-head lettuce. The experimental comparative results indicated that the shoot and root (fresh and dry) weight, root-to-shoot ratio, chlorophyll contents, CWC, NUE, DDPH, H2O2, FRAP, TPC, TFC, nitrate, vitamin C, and protein level were significantly (p<0.05) higher in T2 treatment, and the values were significantly (p<0.05) lower in T1 followed by T5 treatment. Moreover, as mentioned earlier, the median values of the above-mentioned parameters were measured in aeroponics systems with low-pressure nozzle (T3). It also found a strong positive correlation (r>0.7) among the Shoot (FW), Chlorophyll, RWC, NUE, and among TPC, TFC, DDPH, H2O2, and FRAP. This study demonstrates that butter-head lettuce grown in aeroponics systems with high-pressure nozzles may serve as a potential dietary source and is rich in natural antioxidants. Keywords: aeroponics, high-pressure nozzle, phenolic content, antioxidants, lettuce DOI: 10.25165/j.ijabe.20231601.6794 Citation: Tunio M H, Gao J M, Mohamed T M K, Ahmad F, Abbas I, Shaikh S A. Comparison of nutrient use efficiency, antioxidant assay, and nutritional quality of butter-head lettuce (Lactuca sativa L.) in five cultivation systems. Int J Agric & Biol Eng, 2023; 16(1): 95–103.